Comunalidad agroalimentaria frente al capitaloceno - Rossi, Leonardo Javier (2023)
When conceiving ecological and political crisis finds roots in capitalism like an ontological regime, we look for a novel political praxis contributes to heal the social-metabolic web between humans, food, and territories. In this way, the following essay proposes a political epistemology understanding communality as a critical key to design a political ontology against capitalocene.